Unravelling managerial competencies and the profitability of small technology-oriented businesses: A case of public access venues in an emerging economy - Patient Rambe (SA Journal of Human Resource Management, 2018)
Orientation: The tweak speed of technological changes, volatility of domestic markets, shifts in consumer behaviour and homogeneity of Internet-based services are pressurising entrepreneurs operating small technology-oriented businesses such as public access venues (PAVs) (e.g. Internet cafés) to develop a compendium of managerial competencies to deal with these challenges effectively and expeditiously. Yet rigorous research on managerial competencies of Internet café business owners or managers in emerging economies such as South Africa is conspicuously missing, raising critical questions about the perceived significance of such competencies in management and entrepreneurship literature.